(untitled) (Historia, 2021)
Hegemonic Afrikaner masculinity and the ’Other’ in the pre-Apartheid phase : D.C. Boonzaier’ Hoggenheimer caricature The objectrive in the article is to indicate how the concept of the ’Other’ can be used as an analytical instrument in an investigation into the construction of hegemonic masculinity. It is done in the context of an analysis of the facets of D.C. Boonzaaier’s cartoon character Hoggenheimer in Die Burger. First there is a brief theoretoical introduction on hegemonic masculinity and the concept of the ’Other’ There is also a brief sketch of the context in which Boonzaaier operated as a cartoonist. Then follows a few traits of the Hoggenheimer character in specifc relation to the manner in which the ’Other’ was used in the twenties and thirties of the twentieth century in Afrikaner nationalist circles in the process of constructing hegemonic Afrikaner masculinity. Hierdie artikel se oogmerk is om aan te dui hoe die konsep van die ’Ander’ as analitiese instrument gebruik kan word in die ondersoek na die konstruksie van hegemoniese manlikheid. Dit word gedoen aan die hand van ’n ontleding van fasette van D.C. Boonzaier se spotprentkarakter Hoggenheimer in Die Burger.